Problems in Implementing the Independent Curriculum in Arabic Language Subjects at Manu Putra Buntet Islamic Boarding School - Ahmad Gunawan (Yayasan Baru Haji Samsudin, 2025)
Society is always changing, so too the curriculum will experience changes and improvements. Indonesia on a large scale in its educational history, has often experienced curriculum changes, this is based on changes and demands and the needs of students and the same society. The curriculum is a tool used to achieve an educational goal and a guideline for educators in implementing learning at all levels and types of education, without a good and correct curriculum it will be difficult to achieve educational goals and objectives. The problems in this study are problems that arise from the implementation of the independent curriculum due to the incompatibility of the field with the conditions that should be. This study uses a qualitative approach. The type of research is a case study. A case study is a detailed examination of the background or a single subject, or a collection of single documents, or a particular event. Case studies can also be interpreted as research conducted to reveal a situation in depth, intensively, both regarding individuals, individuals, and groups, and community institutions. Based on the findings of the study related to the implementation of the independent curriculum MANU Putra Buntet that the independent curriculum is still not one hundred percent implemented in Madrasah, however there are already classes that implement the independent curriculum, for now only class X MA, and only class X implements it. The principal of MANU Putra Buntet is very influential in overcoming teacher problems in implementing the independent curriculum in Arabic language subjects. Various policies are implemented so that the implementation of the independent curriculum can be successful in this institution. The first thing the principal does is solve all existing problems and then find solutions. Based on the results of research conducted in the implementation of the independent curriculum in Arabic language subjects at MANU Putra Buntet, the Islamic boarding school initially had various problems from the independent curriculum that had not been fully implemented. There are several problematic things in the implementation of the independent curriculum that are being resolved little by little. Among them are the principal's efforts to accommodate the aspirations of teachers, especially Arabic language teachers, through coaching and training in the independent curriculum. After going through several phases and processes, everything became more conducive and better. Keyword: Problems, Independent Curriculum, Arabic